Effects of NAD+ precursor supplementation on glucose and lipid metabolism in humans: a meta-analysis. - Zhong, Ou; Wang, Jinyuan; Tan, Yongpeng; Lei, Xiaocan; Tang, Zhihan (Nutrition & Metabolism, 2022)
Background: This meta-analysis was performed to investigate the effects of nicotinamide adenine dinucleotide (NAD+) precursor supplementation on glucose and lipid metabolism in human body. Methods: PubMed, Embase, CENTRAL, Web of Science, Scopus databases were searched to collect clinical studies related to the supplement of NAD+ precursor from inception to February 2021. Then the retrieved documents were screened, the content of the documents that met the requirements was extracted. Meta-analysis and quality evaluation was performed detection were performed using RevMan5.4 software. Stata16 software was used to detect publication bias, Egger and Begg methods were mainly used. The main research terms of NAD+ precursors were Nicotinamide Riboside (NR), Nicotinamide Mononucleotide (NMN), Nicotinic Acid (NA), Nicotinamide (NAM). The changes in the levels of triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and fasting blood glucose were mainly concerned. Results: A total of 40 articles were included in the meta-analysis, with a sample of 14,750 cases, including 7406 cases in the drug group and 7344 cases in the control group. The results of meta-analysis showed that: NAD+ precursor can significantly reduce TG level (SMD = − 0.35, 95% CI (− 0.52, − 0.18), P < 0.0001), and TC (SMD = − 0.33, 95% CI (− 0.51, − 0.14), P = 0.0005), and LDL (SMD = − 0.38, 95% CI (− 0.50, − 0.27), P < 0.00001), increase HDL level (SMD = 0.66, 95% CI (0.56, 0.76), P < 0.00001), and plasma glucose level in the patients (SMD = 0.27, 95% CI (0.12, 0.42), P = 0.0004). Subgroup analysis showed that supplementation of NA had the most significant effect on the levels of TG, TC, LDL, HDL and plasma glucose. Conclusions: In this study, a meta-analysis based on currently published clinical trials with NAD+ precursors showed that supplementation with NAD+ precursors improved TG, TC, LDL, and HDL levels in humans, but resulted in hyperglycemia, compared with placebo or no treatment. Among them, NA has the most significant effect on improving lipid metabolism. In addition, although NR and NAM supplementation had no significant effect on improving human lipid metabolism, the role of NR and NAM could not be directly denied due to the few relevant studies at present. Based on subgroup analysis, we found that the supplement of NAD+ precursors seems to have little effect on healthy people, but it has a significant beneficial effect on patients with cardiovascular disease and dyslipidemia. Due to the limitation of the number and quality of included studies, the above conclusions need to be verified by more high-quality studies.